(untitled) (Advancements in Homeopathic Research, 2022)
Homoeopathy is a scientific medical alternative for treating a wide range of chronic ailments. The basic approach in homoeopathy is to evaluate the disease of Asthma in its whole extent, where by a lot of emphasis is given to the patient as a whole besides minutely studying various detailed aspects of the Asthma. Homoeopathy treatment is aimed at enhancing body’s own healing capacity so that the human system does not react adversely to the allergens which are considered external factors affecting Asthma. As a rule, homoeopathy never looks at Asthma as a local disease; it has been considered as a local expression of a system disturbance. As per the classical homoeopathy, we believe in constitutional prescribing. This calls for individual case study in every case of Asthma. There is single specific remedy for all the cases of Asthma. The exact treatment is determined only on in depth evaluation of individual case. This is because we do not treat Asthma person, but treats the patient as a whole.